Strategi Pengembangan Kreativitas Pendidikan Anak Usia Dini dalam Pembelajaran - Titin Faridatun Nisa'; Yulias Wulani Fajar (PG-PAUD Trunojoyo, 2016)
Creativity is important to be given early. Therefore, guidance is needed to develop someone’s creativity.  A teacher who is creative will also create a creatively teaching design. The creative learning will make students to be active in developing their own creativities. Developing creativity can be conducted using various ways to build learning climate triggering the development of the ability to think and work. The strategy that can be taken to develop someone’s creativity is by asking some questions that challenge the highest level of thinking process in accordance with the concept of the development of creative ideas, also creative and innovative work. The questions given are categorized based on the profile map of someone’s creativity (i.e.) the imaginative individual profile, investment, improver, and incubating idea.